The Missing Minister of Religion and the PSII: A Contextual Biography of K.H. Ahmad Azhary - Kevin W. Fogg (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
This article provides a contextual biography of K.H. Ahmad Azhary, who was appointed as the Minister of Religion in the first Amir Sjarifuddin cabinet of the Republic of Indonesia in 1947. The life of this man provides insight into Islamic activity in South Sumatra and its connections with the Middle East, as well as with the rest of Indonesia. Most importantly, the examination of Azhary’s appointment to the Indonesian cabinet — to a position that he was never able to hold — shines light onto the circumstances of the exit of Partai Sarekat Islam Indonesia (PSII, Indonesian Islamic Union Party) from Masjumi. Contradictory evidence about the reasons for the exit as presented in PSII and Masjumi sources are evaluated in light of Azhary’s appointment and inability to join the cabinet. The article finds that PSII’s rhetoric about initiative from the provinces to split from Masjumi was probably based on truth.DOI: 10.15408/sdi.v20i1.348